Efficacy and safety evaluation of acupuncture in the treatment of impaired glucose regulation: A protocol for systematic review and meta-analysis. Issue 50 (17th December 2021) - Sun, Jiabao; Wang, Gaofeng; Zhi, Xiaoyu; Zhao, Xuewei; Sun, Weichen; Chu, Yunjie; Wu, Xingquan
Abstract: Background: Impaired of glucose regulation belongs to the stage of prediabetes, which is a state of glucose metabolism between diabetes and normal blood glucose. The prevalence of prediabetes in people over 20 years old in China is significantly higher than that in diabetic patients. If no measures are taken to prevent the transition from prediabetes to diabetes, the number of diabetic patients in China will further increase. This study conducted a meta-analysis of the effectiveness of acupuncture in the treatment of impaired glucose regulation by collecting relevant literatures. Methods: Nine electronic databases: PubMed, EMBASE, Cochrane library, Web of Science, Google Scholar, China National Knowledge Infrastructure, Chinese Biomedical Literature Database, Chinese Scientific and Journal Database, Wan Fang database, and 2 clinical trials register platforms: Chinese Clinical Trial Registry, ClinicalTrials.gov (www.ClinicalTrials.gov/ ) will be searched for randomized clinical trails of acupuncture for impaired glucose regulation. The screening process will be developed by 2 independent reviewers, and meta-analysis will be performed with RevMan (V5.3.5) software. Results: This meta-analysis further confirmed the benefits of acupuncture in the treatment of impaired of glucose regulation. Conclusion: This study will provide a high-quality evidence of the efficacy and safety of acupuncture on patients with impaired glucose regulation. PROSPERO registration number: INPLASY202170058. Ethics and dissemination: This systematics review will evaluate the efficacy and safety of acupuncture in the treatment of impaired of glucose regulation. Since all the data included were published, the systematic review did not require ethical approval.